FIELD TEST STUDY ON THE PERFORMANCE OF SIX-BLADE SPIRAL HORIZONTAL AXIS WIND TURBINE RELATED TO THE EFFECT OF SOLIDITY NUMBER - Remboko, Remboko; Hamid, Abdul (Universitas Mercu Buana, 2024)
Fossil fuels are still a daily necessity in the world. Human dependence on fossil fuels has created problems related to pollution and energy security. Wind turbines are renewable energy power plants where their use is expected to be an unlimited alternative energy source. This wind turbine research uses a field test study method with a six-blade spiral horizontal axis wind turbine (TASH) type. TASH performance is assessed by measured parameters such as rated voltage, generator output current and torque value; also non-dimensional parameters such as power coefficient, Cp, torque coefficient, Ct and Tip Speed Ratio, TSR values generated due to TASH rotation at every wind speed from 3.0 m/s to 4.5 m/s wind speed. Field test results obtained: Actual power (experimental) = 5.50 Watt and torque value = 10.7 N.m at a wind speed of 4.5 m/s. Cp = 0.0083, Ct = 1.2180, and TSR = 0.0068 at a wind speed of 3.0 m/sThe solidity value obtained based on the calculation results is 1.627 for a 5-blade wind turbine, while for a 6-blade and 8-blade wind turbine, the solidity values are 1.953 and 2,604. As the turbine solidity value increases, the power coefficient will also increase, inversely proportional to the torque coefficient, that as the turbine solidity value increases, the torque coefficient will decrease